Groundwater quality and quantity, and irrigation requirement for oil palm plantations in peat swamp, south Selangor, Malaysia - Richard, Adesiji Adeolu (2016)
As a result of boom recorded globally in oil palm industries, many countries, especially in the Southeastern Asia region such as Malaysia and Indonesia have converted sizeable parts of their peat swamp forests to oil palm plantation. Prior to this conversion, these peat swamp forests had been the most important terrestrial ecosystem for carbon storage, regulating greenhouse gas emission and climate, and a source of water supply and flood control, particularly for the neighboring communities. Therefore, the conversion of the peat swamp forests for the purpose of agricultural practices which is oil palm plantations has done more damages than good.Cultivation of oil palms on peat soil has greatly affected the environment and soil carbon in recent time, especially when such practice has been on for several years. Large concentrations of carbon stored in the peats over the years is being exposed to the atmosphere as a result of this indiscriminate land conversion for agricultural purposes and this has further aggravated the issue of global warming by increasing the amount of greenhouse gases in the atmosphere.The water quality degradation is another negative effect of this practice. Due to the anthropogenic activities being practiced on the peatlands, soil carbon are escaping into the groundwater in dissolved form as dissolved organic carbon which seeps and pollutes the peatland streams which feed the adjoining rivers thereby becoming a source of pollution to the rivers used for municipal water supply.This study therefore considers four main objectives including the best management practices or policies needed for greater outputs from the peatlands. The first objective considered the effects of oil palm plantation on soil chemistry with respect to different age of plantations. Soil analyses were carried out and the parameters considered in soil analyses are; pH, moisture content, carbon, nitrogen, sulphur, and some heavy metals like, manganese, zinc, iron, copper, and phosphorus. Heavy metals present in the soil were determined using the double acid method while carbon, nitrogen, and sulphur were determined using flash combustion method.The results of the soil analysis indicated both strong and weak correlations among carbon, nitrogen, sulphur, depth and pH during both dry and wet periods. During the dry period, carbon values ranged from the highest (49.07%) in the oil palm cultivated in the year 2000 to the lowest (11.66%) in 2010-cultivated oil palm. During the wet season, soil carbon ranged from highest 51.22 % at 0.5 m depth in 2000 study plot to the lowest as 37.04 % at 1.5 m depth in 2002 study plot. This suggests that soil carbon content of peat soil shows some levels of correlation with depth during the dry season as against the wet season. In other words, there is weak correlation of soil carbon with age of plantation and soil depth in dry season and none during the wet season. However, peat soil during the wet season recorded higher soil carbon content.The second study focused on the hydrological influence on concentration of dissolved organic carbon (DOC) in both peatland groundwater and surface water with emphasis on rainfall distribution pattern and fluctuation in groundwater table. The result showed that the highest flux of DOC was observed during the high storm events and high water table while the lowest flux was observed when the groundwater table was at the lowest level. This shows that the hydrological factor is a significant factor for determining the peatland DOC flux.Having established the link between the groundwater table and DOC flux, the third objective focused on the drivers of groundwater table fluctuation. The two drivers noted were soil moisture and soil temperature. With soil moisture probe and soil temperature sensors buried into the soil at two different depths of 5 cm and 70 cm, and pressure transducers inserted through a tube well into the groundwater in 10 different locations, the daily soil moisture and temperature at both depths and daily water table depths were determined over the period of 6 months. The results were collected from loggers with the aid of computer laptop and were analyzed using multiple linear regression of SPSS. The results showed significant relationship between precipitation, soil temperature and soil moisture at both 5 cm and 70 cm soil depths (70 cm in particular). The result also showed significant relationship between soil moisture at both depths and groundwater table fluctuations. However, there is no significant relationship between soil temperatures at both depths with groundwater table fluctuations.The fourth objective considered the groundwater recharge and soil moisture deficit estimation for the study area. The two parameters of soil moisture balance model were used to estimate the water requirement of the oil palms in all the study plots. The study plots were divided into four plots: 2000, 2002, 2006 and 2010, based on the years of peat swamp forest conversion to oil palm plantation. Two different hydrological models were used in this study. Hydrologic Modeling System, HEC-HMS was used along with recorded flow and rainfall data to establish a rainfall-runoff relationship for a nearby catchment which was calibrated and later validated before being used in the study area. HEC-HMS discharge values were adopted as observed flow and compared with soil moisture balance model. Soil moisture balance model was also calibrated and validated and used to check soil moisture status of oil palm in daily time step. Periods with water deficit for oil palms in all the study periods were observed and the irrigation water needs were estimated for each of the study plots. For 2000 study plot, the irrigation water need was estimated as 1.6 x 10⁶ m₃, 0.689 x 10⁶ m₃ for 2002 study plot, 0.607x 10⁶ m₃ for 2006 study plot and 0.893 x 10⁶ m₃ for 2010 study plot. Irrigation water need of a plantation is therefore observed to be site specific which depends on the soil moisture deficit, readily available water in the oil palm root zone and oil palm rooting depth. River Labu, with basin of 260.72 km2 was proposed as a source of irrigation water. The estimation of daily runoff discharge from Seventeen sub-basins of River Labu basin showed that the basin could provide the needed irrigation requirement for the four study plots. Estimation of a future oil palm water requirement using the soil moisture balance model would be recommended for further studies so as to aid in using the model as an advisory manual for the oil palm managers in order to enhance adequate water resources planning for oil palm productivity.